Low-storage temperature effects on the quality of carabao mangoes - Manasan, Ma. Virginia F.; De Leon, Sonia Y. (1967)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Mango -- Storage